If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 9 = 9x + 11 Reorder the terms: 9 + 10x = 9x + 11 Reorder the terms: 9 + 10x = 11 + 9x Solving 9 + 10x = 11 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 9 + 10x + -9x = 11 + 9x + -9x Combine like terms: 10x + -9x = 1x 9 + 1x = 11 + 9x + -9x Combine like terms: 9x + -9x = 0 9 + 1x = 11 + 0 9 + 1x = 11 Add '-9' to each side of the equation. 9 + -9 + 1x = 11 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 11 + -9 1x = 11 + -9 Combine like terms: 11 + -9 = 2 1x = 2 Divide each side by '1'. x = 2 Simplifying x = 2
| 0.5x=0 | | 64y=7(9y-5) | | 56a^2-17a-3= | | 25x^3-24x+8=0 | | 3z-5=10-2z | | (-1/5)*3= | | 141-5x=5x-21 | | 110-3x=24x+17 | | 121-2x=16x+21 | | X^2+5+20=0 | | -1/5*-1/5*-1/5= | | X^2+1x+1=0 | | 5-9x=63-23x | | 7=5-x | | X^2=5-6x | | 10b^2-29b+10= | | ln(x)+ln(x+6)=ln(7) | | 4x+10-9x=17-15x+10x-7 | | 3(x+2)-2(1-x)=4x+5 | | 5x^2+6x+3=0 | | 120-5x=13x+20 | | 8x-(5x+4)=17 | | 4x-4=13x-74 | | 15b^2-34b+15= | | 7x+80=5(20+x) | | 125-4x=4x+21 | | 3(3+6x)-4=113 | | 2x^2=11x+6 | | 2y-3=-1 | | -8t-3=-67 | | -4(4y-7)+2(2y+6)= | | 5-7=43 |